One-Step Synthesis of N, P-Codoped Carbon Nanosheets Encapsulated CoP Particles for Highly Efficient Oxygen Evolution Reaction - Liu, Yuchuan; Guan, Xu; Huang, Baobing; Wei, Qiaohua; Xie, Zailai (Frontiers in Chemistry, 2020)
Oxygen electrocatalysis, especially oxygen evolution reaction (OER) is a central process during the actual application of continuous fuel cells and rechargeable metal-air battery. It is still challenging to develop ideal electrocatalyst to substitute the commercial noble metal-based materials. In this work, we have constructed a new material that CoP nanoparticles which are encapsulated by a biomolecule derived N, P-codoped carbon nanosheets via a simple and facile one-step strategy. The as-prepared material releases a high electrocatalytic activity and stability for OER, with an overpotential of 310 mV to achieve 10 mA/cm 2 in 1 M KOH. Importantly, we found that the phosphoric acid can not only introduce phosphorus dopant into 2D N-doped carbon nanosheets and play a role of porogen agent, but also participate in the formation of active center (cobalt phosphide).Moreover, the coverage of N, P-carbon can prevent the CoP nanoparticles from aggregation under the harsh reaction medium to achieve high and stable activity. We believe our strategy can offer a novel pathway to synthesize new transition metal based catalysts for electrocatalysis or other heterogeneous catalysis.